2015
DOI: 10.3389/fpsyg.2015.00545
|View full text |Cite
|
Sign up to set email alerts
|

Performance-based tests versus behavioral ratings in the assessment of executive functioning in preschoolers: associations with ADHD symptoms and reading achievement

Abstract: The early assessment of the executive processes using ecologically valid instruments is essential for identifying deficits and planning actions to deal with possible adverse consequences. The present study has two different objectives. The first objective is to analyze the relationship between preschoolers’ performance on tests of Working Memory and Inhibition and parents’ and teachers’ ratings of these executive functions (EFs) using the Behavior Rating Inventory of Executive Function (BRIEF). The second obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 58 publications
(77 reference statements)
1
44
0
4
Order By: Relevance
“…It should be noted at this point that early research on multiple informants in child and adolescent psychopathology (see Smith, 2007 for a review) generally suggested that for older children the child is often the best informant, followed by parent and then teacher reports. However, recent studies (Dekker, Ziermans, Spruijt, & Swaab, 2017;Miranda et al, 2015) using the BRIEF rating scales supported the reverse pattern. These studies included both parent and teacher-report BRIEF EF ratings in order to examine the relative impact of these different EF ratings on social outcomes and indicated that it is the teacher EF ratings along with performance-based EF that have a complementary role in outcome variables (parent-report EF ratings explained significantly less or not at all variance).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…It should be noted at this point that early research on multiple informants in child and adolescent psychopathology (see Smith, 2007 for a review) generally suggested that for older children the child is often the best informant, followed by parent and then teacher reports. However, recent studies (Dekker, Ziermans, Spruijt, & Swaab, 2017;Miranda et al, 2015) using the BRIEF rating scales supported the reverse pattern. These studies included both parent and teacher-report BRIEF EF ratings in order to examine the relative impact of these different EF ratings on social outcomes and indicated that it is the teacher EF ratings along with performance-based EF that have a complementary role in outcome variables (parent-report EF ratings explained significantly less or not at all variance).…”
Section: Introductionmentioning
confidence: 95%
“…In fact everyday EF ratings may show a greater capacity to predict clinical symptoms related to developmental disorders (e.g. ADHD, ASD) (Miranda, Colomer, Mercader, Ferna´ndez, & Presentacio´n, 2015). Considering thus that performance-based and rating scales may index different level of cognitive analysis and that the behavioural outcomes measured by ratings such as the BRIEF occur in social contexts and relate to individuals' everyday lives, it would be important to study these EF behavioural manifestations from a developmental perspective in order to shed more light on the heterogeneity of the developmental profiles of children and adolescents with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Both measurements systems have their limitations. Behaviors performed in an artificial, controlled setting, such as a laboratory, will necessarily differ from behaviors that occur in a natural everyday setting, and therefore any findings will have low ecological validity (Miranda, Colomer, Mercader, Fernández, & Presentación, 2016). On the other hand, while information supplied by third parties can provide insights into a greater number of situations, its reliability is questionable for numerous reasons related to, for instance, social desirability or recall bias, and even a lack of familiarity or sensitivity on the part of the observer to perceive and detect certain behaviors (Wertz, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Mood disorders included. Performance-based tests versus behavioral ratings in the assessment of executive functioning in preschoolers: associations with ADHD symptoms and reading achievement 2015 Journal Frontiers in Psychology SPAIN Miranda, Colomer, Mercader, Fernández, Presentación (26) The first objective is to analyze the relationship between preschoolers' performance on tests of Working Memory and Inhibition and parents' and teachers' ratings of these executive functions using the Behavior Rating Inventory of Executive Function. The second objective consisted of studying the predictive value of the different EF measures (performance-based test and rating scales) on ADHD symptoms and on indicators of word reading performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This influences the academic tasks associated with reading fluency and processing. Performance-based tests versus behavioral ratings in the assessment of executive functioning in preschoolers: associations with ADHD symptoms and reading achievement (26) 209 children in the last preschool year, their teachers and their families. public schools (63.3%); private schools subsidized by the government (30.6% ); and private schools (5.9%).…”
mentioning
confidence: 99%